2005
DOI: 10.1007/s00167-005-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary stability of four different implants for opening wedge high tibial osteotomy

Abstract: Since a significant number of implant failures have been reported in association with the procedure of open wedge valgus high tibial osteotomy, the initial biomechanical stability of different fixation devices was investigated in this study. Fifteen third generation Sawbones composite tibiae were used as a model. Four different plates were tested: a short spacer plate (OWO) (n = 4), a short spacer plate with multi-directional locking bolts (MSO) (n = 5), a prototype version of a long spacer plate with multi-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
176
2
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(209 citation statements)
references
References 15 publications
12
176
2
12
Order By: Relevance
“…Furthermore, it has been suggested that instability resulting from a fracture of the lateral cortical hinge could lead to nonunion. Mechanical studies have shown that when the lateral tibial cortex is fractured, angle-stable implants provide superior stability compared with nonangle-stable implants, eg, the Puddu plate [1,14,19]. The present study shows that for open wedge HTO fixed using an angle-stable implant, fracture of the lateral cortical hinge is not a risk factor for developing nonunion.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Furthermore, it has been suggested that instability resulting from a fracture of the lateral cortical hinge could lead to nonunion. Mechanical studies have shown that when the lateral tibial cortex is fractured, angle-stable implants provide superior stability compared with nonangle-stable implants, eg, the Puddu plate [1,14,19]. The present study shows that for open wedge HTO fixed using an angle-stable implant, fracture of the lateral cortical hinge is not a risk factor for developing nonunion.…”
Section: Discussionmentioning
confidence: 48%
“…Factors that can lead to problems in bone healing are loss of correction resulting from hardware failure [4,16,20] and lateral cortical hinge fracture [1,19,22]. In the past decade, new angle-stable fixation implants have made the medial open wedge HTO technique more popular as a result of the higher loading capacity and the high residual stability after failure of the lateral cortex [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agneskirchner et al [2] compared four different plates: (1) short spacer plate, (2) short spacer plate with multi-directional locking screws, (3) long spacer plate with multi-directional locking screws and (4) long medial tibia plate fixator with locking screws. They stated that a rigid long plate fixator with angle stable locking screws yields the best results.…”
Section: Type Of Fixationmentioning
confidence: 99%
“…By using the TomoFix™ plate, a fixation without cancellous bone transplantation has become possible (Lobenhoffer and Agneskirchner, 2003;Staubli et al, 2003). Biomechanical investigations in sawbone models showed a high primary stability with a limit of 1 606 N in axial load (Agneskirchner et al, 2006). In our case, a biplanar osteotomy after the failed dome-shaped HTO was not possible due to the non-union in the dome-shaped osteotomy.…”
mentioning
confidence: 71%